Three new species of thelotremoid Graphidaceae from tropical Africa - Lücking, Robert (Phytotaxa, 2014)
Three new species of thelotremoid Graphidaceae are described from tropical Africa. Astrochapsa fusca Lücking differs from A. platycarpella in the brown thallus and larger ascospores with more numerous septa. Ocellularia abbayesiana is similar to O. exuta in morphology and chemistry but has smaller, hyaline ascospores. Ocellularia grantii resembles O. terebrata in the carbonized excipulum and columella, the hyaline, transversely septate ascospores, and the psoromic acid chemistry, but is distinguished by its verrucose-bullate thallus, white-tipped columella, and smaller ascospores. The three species were discovered in historic material collected between 1874 and 1954 and underline the importance of revising herbarium collections for the discovery of novel taxa.